Écrire (entre) ses langues en atelier d’écriture - Noëlle Mathis (Carnets)
During creative writing workshops at university with French as a Second Language adult students, I use the works of published authors who navigate amongst several languages in their writing. In this article, I attempt to show how these texts offer a kind of legitimation to students so that they also use their plurilingual repertoire and identities in their literacy practices as a way to improve language competencies.